Developing Sidoarjo Local Wisdom-Based Instructional Materials via Genially Interactive Multimedia to Enhance Students’ Self-Regulated Learning and Digital Literacy - Asnimawati Asnimawati; Andi Gunawan; Radinal Fadli (PUSAKA: Journal of Educational Review, 2026)
Education in the 21st century requires students to possess adequate digital literacy and self-regulated learning skills. However, classroom observations and needs analysis revealed that students still face difficulties in ICT literacy, critical evaluation of digital information, and digital ethics. This study aimed to develop and validate local wisdom-based Social Studies instructional materials integrated with Genially interactive multimedia to enhance these competencies. This Research and Development (R&D) study employed the ADDIE model, covering the Analysis, Design, Development, and limited Implementation stages. Data were collected through interviews, observations, questionnaires, expert validation, and practicality assessments involving teachers and students in a small-scale trial. The developed instructional materials integrated Sidoarjo local wisdom with Genially's interactive and gamified features to support project-based learning. Expert validation indicated that the instructional model (87.7%), interactive multimedia (88.4%), and instructional materials (86.5%) were categorized as highly feasible. Furthermore, the limited implementation results demonstrated high practicality, with teacher and student practicality scores of 90.80% and 93.17%, respectively. These findings suggest that the developed instructional materials provide a feasible and practical approach to promoting students' digital literacy and self-regulated learning through culturally relevant interactive learning.